Intelligent computing in bioinformatics : 10th International Conference, ICIC 2014, Taiyuan, China, August 3-6, 2014. Proceedings - Han, Kyungsook; Gromiha, Michael; Huang, De-Shuang (Lecture Notes in Computer Science, 2014)
This book - in conjunction with the volumes LNCS 8588 and LNAI 8589 - constitutes the refereed proceedings of the 10th International Conference on Intelligent Computing, ICIC 2014, held in Taiyuan, China, in August 2014. The 58 papers of this volume were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections such as machine learning; neural networks; image processing; computational systems biology and medical informatics; biomedical informatics theory and methods; advances on bio-inspired computing; protein and gene bioinformatics: analysis, algorithms, applications.